2020
DOI: 10.3390/ani10071152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paper Mulberry Silage on the Milk Production, Apparent Digestibility, Antioxidant Capacity, and Fecal Bacteria Composition in Holstein Dairy Cows

Abstract: Paper mulberry (Broussonetia papyrifera; PM) is an excellent and extensive type of roughage in Asia. This study aimed to evaluate the effects of PM silage on the milk production, apparent digestibility, antioxidant capacity, and fecal bacteria composition in Holstein dairy cows. Forty-five lactating Holstein dairy cows with a similar milk yield and parity were selected and randomly assigned to three groups. The control group was fed a non-PM silage diet, and the PM-treated groups were fed 4.5 and 9.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…The activities of serum SOD, CAT and POD rose to the highest levels, while MDA content declined to its lowest level following the addition of 5% FMLs to the feed, indicating that 5% FMLs effectively improved the crucian antioxidant capacity, which result was consistent with that pertaining to Hosltein dairy cows (Hao et al, 2020) and laying hens (Lin et al, 2017). However, the activities of SOD, CAT and POD were inhibited when the content of FMLs was too high (>10%), which was consistent with the results of studies on water buffaloes (Li et al, 2020) and tilapia (Miao et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…The activities of serum SOD, CAT and POD rose to the highest levels, while MDA content declined to its lowest level following the addition of 5% FMLs to the feed, indicating that 5% FMLs effectively improved the crucian antioxidant capacity, which result was consistent with that pertaining to Hosltein dairy cows (Hao et al, 2020) and laying hens (Lin et al, 2017). However, the activities of SOD, CAT and POD were inhibited when the content of FMLs was too high (>10%), which was consistent with the results of studies on water buffaloes (Li et al, 2020) and tilapia (Miao et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…[ 22 , 45 , 46 ]. Our previous studies have shown that adding 4.5–18.0% PM silage (substituting the alfalfa and oat grass) to the diet did not affect the total-tract apparent digestibility of dairy cows [ 47 ]. However, in this study, we proved that the different parts of PM had distinct digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…DNA concentration and purity were determined using the NanoDropND-1000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA). The V3-V4 region of the 16S rRNA gene was amplified according to the method described in Hao et al [21]. As Guo et al [22] reported, the former primer sequence of 341F (CCTACGGGNGGCWGCAG) and the reverse sequence of 806R (GGACTACHVGGGTATCTAAT) were used.…”
Section: Dna Extraction and Determinationmentioning
confidence: 99%